2019
DOI: 10.30880/ijie.2019.11.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Stitching Patterns on Tensile Strength of Kenaf Woven Fabric Composites

Abstract: In the recent decades, natural fibre has become one of the major interesting research subjects due to its lightweight, tool wear reduction, thermal isolation properties, renewable and has suitable specific mechanical properties [1], [2]. Natural fibres are commonly used in non-structural and non-load bearing components applications by using non-woven

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…The study found that composites with a plain weave structure provided better mechanical strength compared to a random composite orientation, suggesting that the woven structure affected the mechanical properties of the composite. Yaakob et al [ 92 ] compared the inclusion of stitches on the woven kenaf fabric in other studies in order to increase the strength of the through-thickness, the resilience of the interlaminar fracture, and the tolerance of impact damage between the polymer matrix and reinforcement. On the fabric of the kenaf woven, as shown in Figure 9 , eight types of stitching patterns focusing on stitch patterns and angles were used.…”
Section: Factors Influencing Woven Polymer Composites Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The study found that composites with a plain weave structure provided better mechanical strength compared to a random composite orientation, suggesting that the woven structure affected the mechanical properties of the composite. Yaakob et al [ 92 ] compared the inclusion of stitches on the woven kenaf fabric in other studies in order to increase the strength of the through-thickness, the resilience of the interlaminar fracture, and the tolerance of impact damage between the polymer matrix and reinforcement. On the fabric of the kenaf woven, as shown in Figure 9 , eight types of stitching patterns focusing on stitch patterns and angles were used.…”
Section: Factors Influencing Woven Polymer Composites Propertiesmentioning
confidence: 99%
“… ( a ) Woven fabric from kenaf yarn with plain weave pattern ( b ) types of stitch patterns used in this study. Source: Figure reproduced with copyright permission from Yaakob et al [ 92 ]. This article is an open-access article distributed under the terms and conditions of the Creative Commons Attribution (CC BY) license ( ).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…More importantly, WKS/X stitched specimens have higher tensile strength compared to the unstitched specimens. Yaakob et al [25] also agreed with this claim. Figure 11 shows the effect of stitching pattern and density on the tensile strength and modulus of the unstitched and silk-fiber-stitched woven kenaf composites.…”
Section: Tensile Test Resultsmentioning
confidence: 76%
“…Mohd Yuhazri Yaakob et al [25] studied the effect of stitching patterns on the tensile strength of kenaf woven fabric composites. In their study, the woven kenaf was stitched with two different patterns, which were the single-stitched pattern and double-cross pattern.…”
Section: Introductionmentioning
confidence: 99%